LRH-1 senses signaling from phosphatidylcholine to regulate the expansion growth of digestive organs via synergy with Wnt/β-catenin signaling in zebrafish. (20th June 2017) - Zhai, Gang; Song, Jia; Shu, Tingting; Yan, Junjun; Jin, Xia; He, Jiangyan; Yin, Zhan
Abstract: Liver receptor homolog-1 (LRH-1) is an orphan nuclear receptor that is critical for the growth and proliferation of cancer cells and other biological processes, including lipid transportation and metabolism, sexual determination and steroidogenesis. However, because homozygous lrh-1 −/− mice die in utero, the regulatory mechanisms involved in embryonic development mediated by this receptor are poorly understood. In the present study, we performed transcription activator-like effector nuclease (TALEN)-mediated loss-of-function assays, taking advantage of zebrafish external fertilization, to investigate the function of lrh-1 . The digestive organs were affected by lrh-1 depletion as a result of cell-cycle arrest (at the checkpoint of G1 to S phase), but not cell apoptosis. Biochemical analysis revealed that LRH-1 augments the transcriptional activity of β-catenin 1 and 2 via physical interactions. Screening the specific ligand(s) sensed by LRH-1 during organogenesis revealed that phosphatidylcholine (PC), a potential ligand, is the upstream target of LRH-1 during endoderm development. These data provide evidence for the crosstalk between the PC/LRH-1 and Wnt/β-catenin signaling pathways during the expansion growth of endoderm organs.